Drug resistance in inflammatory bowel diseases. (December 2015) - Moreau, Jacques; Mas, Emmanuel
Highlights: Treatment goal evolves from clinical remission to mucosal healing or deep remission. Thiopurines are poorly effective in adults and had severe adverse events. Anti-TNFα should be rapidly used in severe patients. Drug development is mandatory, addressing new targets. Abstract : The management of patients with moderate to severe inflammatory bowel diseases, that is, Crohn's disease and ulcerative colitis, remains challenging. In recent years, therapeutic goal evolved from clinical remission to mucosal healing and deep remission. In order to achieve remission, it is important to appropriately choose and use available drugs. Therefore, anti-TNFα treatment should be rapidly used for severe and at-risk patients, sometimes in association with thiopurines or methotrexate. The monitoring of through levels and antibodies to anti-TNFα is relevant to optimize the treatment and to reduce drug inefficacy. However, the development of new drugs is required to offer alternative tools to severe and refractory patients.